2014
DOI: 10.1002/lpor.201400058
|View full text |Cite
|
Sign up to set email alerts
|

Orthorhombic YAlO3 – a novel many‐phonon SRS‐active crystal

Abstract: In single crystals of orthorhombic YAlO3, widely known as a host‐matrix for Ln3+‐lasant ions, many‐phonon stimulated Raman scattering interactions as well as different manifestations of cascaded and cross‐cascaded nonlinear χ(3)↔χ(3) processes are initiated by picosecond laser pulses. The scientific and applicative potential of YAlO3 crystals is considerably expanded by the demonstration of its SRS properties. In particular, the studies revealed the manifestation of eight χ(3)‐active vibrational modes. The cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…It is known that orthorhombic perovskite YAlO 3 (YAP) has many applications as a thermally stable inorganic crystal. For example, it can be used as a laser [4][5][6][7][8] and a scintillator, [9][10][11] since it emits luminescence when ions of rare-earth metals such as Nd 3+ and Yb 3+ are doped. In addition, Nd:YAP is expected as a candidate for a compact and powerful laser in a THz frequency range.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that orthorhombic perovskite YAlO 3 (YAP) has many applications as a thermally stable inorganic crystal. For example, it can be used as a laser [4][5][6][7][8] and a scintillator, [9][10][11] since it emits luminescence when ions of rare-earth metals such as Nd 3+ and Yb 3+ are doped. In addition, Nd:YAP is expected as a candidate for a compact and powerful laser in a THz frequency range.…”
Section: Introductionmentioning
confidence: 99%
“…6) Recently, more scientists have begun to pay more attention to the search for new SRS-active crystals. [7][8][9][10] After the first discovery of Fresnoite Ba 2 TiSi 2 O 8 (BTS) crystals in Sanbornite-bearing metamorphic rocks in California, 11) many technologically important functional properties of Ba 2 TiSi 2 O 8 crystals, such as nonlinear optical, electrooptical, elasto-optical, photoconductive, piezoelectric, surface acoustic wave, and UV luminescence properties with long decay times, have been studied. [11][12][13][14][15][16][17][18][19][20] Besides the comprehensive exploration and investigation of new properties of Ba 2 TiSi 2 O 8 crystals, it is extremely important to search for new SRS-active crystals, and this is the starting point of the research reported here.…”
mentioning
confidence: 99%